2008
DOI: 10.1111/j.1755-6686.2008.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

BUTTONHOLE CANNULATION: SHOULD THIS BECOME THE DEFAULT TECHNIQUE FOR DIALYSIS PATIENTS WITH NATIVE FISTULAS?
Summary of the EDTNA/ERCA Journal Club discussion Autumn 2007

Abstract: The paper discussed during autumn 2007 was a report entitled 'Cannulating in haemodialysis: rope-ladder or buttonhole technique?' published in Nephrology Dialysis Transplantation. The authors agreed to follow the discussion and respond to points raised. Twenty-three expert contributors from 13 different countries provided evidence, opinion and historical insights into vascular access techniques for chronic haemodialysis patients. All contributors who had introduced the buttonhole technique for patients with na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 3 publications
0
27
0
5
Order By: Relevance
“…The risk of developing these complications has been suggested to be greater with the standard rope ladder technique rather than buttonhole technique [17]. If this is correct, then why has the buttonhole technique not become more universally practiced?…”
Section: Discussionmentioning
confidence: 99%
“…The risk of developing these complications has been suggested to be greater with the standard rope ladder technique rather than buttonhole technique [17]. If this is correct, then why has the buttonhole technique not become more universally practiced?…”
Section: Discussionmentioning
confidence: 99%
“…Enormous dilatation (aneurysms) develops in some patients. The puncture technique plays a substantial role in the development of aneurysms [52,53] . Basically, 3 methods of access cannulation are used: (1) rope ladder cannulation (changing the puncture sites along the access); (2) area puncture cannulation (punctures within a short access segment), and (3) buttonhole technique (punctures into exactly the same sites).…”
Section: Outflow Veinmentioning
confidence: 99%
“…The BH technique was initially introduced with hopes of preserving access in short AVFs (5). The perceived benefits of reduction in problematic cannulation episodes (4,(6)(7)(8) and patient discomfort and lower requirement for AVF interventions have led to a resurgence in the use of BH cannulation, specifically in the home hemodialysis (HHD) setting (6,7,(9)(10)(11)(12)(13). Recent studies have suggested increased infections in patients using BH cannulation; however, definitive evidence is lacking (8,10,14).…”
Section: Introductionmentioning
confidence: 99%